Kajian Literatur Konseling Kelompok Kunci untuk Meningkatkan Keterampilan Sosial - Avrila Aura Sayyidhina; Olivia Maharani; Hany Natari Adha; Defri Yani; Ratna Sari Dewi (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
Social skills are one of the important aspects for students' social life, especially in building healthy interpersonal relationships, and adapting to their school environment. However, some students experience difficulties in socializing both with peers and their school environment, which will have an impact on the lack of confidence in students and face social anxiety. Research was conducted to identify the effectiveness of group counseling in improving students' social skills. This research uses a literature review method using journals from the last 5 years. The result of this study is that group counseling is an effective intervention in improving students' social skills.